Opportunity for change: Undergraduate training in family medicine - Olukayode A. Adeleke; Busisiwe Cawe; Parimalaranie Yogeswaran (South African Family Practice)
The coronavirus disease 2019 (COVID-19) pandemic has changed the world as we knew it, and medical education is not an exception. Walter Sisulu University (WSU) has a distributed model of clinical training for the Bachelor of Medicine and Bachelor of Surgery (MBChB) programme. To address the challenges occasioned by the pandemic, the Department of Family Medicine and Rural Health undertook a modification of its MBChB VI programme. The changes aim to ensure the protection of all stakeholders and maintain the integrity of the programme, including the assessment. Changes were made in the delivery of the programme and in the way people interact with one another. Continuous assessment was modified, and the oral portfolio examination was introduced as the summative assessment tool. Although COVID-19 threatened the traditional way of teaching and learning, it however provided us with the opportunity to refocus and reposition our undergraduate medical programme.